The future of computing Innovation start-ups get leaner and reach further . IN The New York Times. - Lohr, Steve (Manila Bulletin)
What's next? If we had a supercomputer that could predict the future, we would tell you. But if the past is any guide, the prediction would certainly be wrong. Here are some technologies that are changing the world.